p/t băng nhóm hạng tử
a\(^2\)+ab+2b-4
x^3-4x\(^2\)-8x+8
x\(^2\)-y\(^2\)+2yz-z\(^2\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(4x^2\left(x+3\right)-8x\left(3+x\right)=4x\left(x+3\right)\left(x-2\right)\)
b) \(4x^2+y^2-25+4xy=\left(2x+y\right)^2-25=\left(2x+y-5\right)\left(2x+y+5\right)\)
c) \(\left(x-3\right)^2-\left(x+2\right)^2=\left(x-3-x-2\right)\left(x-3+x+2\right)=-5\left(2x-1\right)\)
a) \(8x^3+27=\left(2x+3\right)\left(4x^2-6x+9\right)\)
b) \(4x^2-4x+1-y^2=\left(2x-1\right)^2-y^2=\left(2x-1-y\right)\left(2x-1+y\right)\)
c) \(x^4-2x^3+x^2-2x=x^3\left(x-2\right)+x\left(x-2\right)=x\left(x-2\right)\left(x^2-1\right)=x\left(x-2\right)\left(x-1\right)\left(x+1\right)\)
d) \(x^2-4y^2+2x+4y=\left(x-2y\right)\left(x+2y\right)+2\left(x+2y\right)=\left(x+2y\right)\left(x-2y+2\right)\)
\(Bài1:\\ a,\left(4x-1\right)\left(2x^2-x-1\right)=4x\left(2x^2-x-1\right)-\left(2x^2-x-1\right)=8x^3-4x^2-4x-2x^2+x+1=8x^3-6x^2-3x+1\\ b,\left(4x^3+8x^2-2x\right):2x\\ =2x\left(2x^2+4x-1\right):2x\\ =2x^2+4x-1\)
\(Bài2:\\ a,2x^3-8x^2+8x=2x\left(x^2-4x+4\right)=2x\left(x-2\right)^2\\ b,2xy+2x+yz+z=2x\left(y+1\right)+z\left(y+1\right)=\left(y+1\right)\left(2x+z\right)\\ c,x^2+2x+1-y^2=\left(x+1\right)^2-y^2=\left(x-y+1\right)\left(x+y+1\right)\)
Ta có: \(A=a^2+ab+2b-4\)
\(\Leftrightarrow\left(a.a\right)+\left(a0+b\right)+\left(20+b\right)-4\)
\(B=x^3-4x^2-8x+8\)
\(\Leftrightarrow\left(x.x.x\right)-\left(40+x\right)^2-\left(80+x\right)+8\)
\(C=x^2-y^2+2yz-z^2\)
\(\Leftrightarrow\left(x.x\right)-\left(y.y\right)+\left(200+y0+z\right)-\left(z.z\right)\)
\(D=5x^3-10x^2+5x\)
\(\Leftrightarrow\left(50.50.50+x.x.x\right)-\left(100+x\right)^2+\left(50+x\right)\)
\(a,=4\left(x-1\right)^2\\ b,=\left(x-y\right)\left(x+y\right)+3\left(x+y\right)=\left(x+y\right)\left(x-y+3\right)\)
a, 4x2 - 8x + 4 = (2x)2 - 2.2x.2 + 2 = (2x - 2)2
b, x2 - y2 + 3x + 3y = (x2 - y2) + (3x + 3y) = (x- y). (x + y) + 3.(x + y) = (x+y).(x- y + 3)
a: =3x(y-2)-5(y-2)
=(y-2)(3x-5)
b: =(2x-5y)(2x+5y)
c: =x(x^3-8)
=x(x-2)(x^2+2x+4)
a)
\(3x\left(y-2\right)+5\left(2-y\right)\\=3x\left(y-2\right)-5\left(y-2\right)\\ =\left(y-2\right)\left(3x-5\right) \)
b)
\(4x^2-25y^2\\ =\left(2x-5y\right)\left(2x+5y\right)\)
c)
\(x^4-8x\\ =x\left(x^3-8\right)\\ =x\left(x-2\right)\left(x^2+2x+4\right)\)
5.
\(4x^5y^2+8x^4y^3+4x^3y^4=4x^3y^2(x^2+2xy+y^2)\)
\(=4x^3y^2(x+y)^2\)
9.
\(4x^5y^2+16x^4y^2-6x^3y^2=2x^3y^2(2x^2+4x-3)\)
13.
\(-3x^4y+6x^3y-3x^2y=-3x^2y(x^2-2x+1)=-3x^2y(x-1)^2\)
17.
\(8x^3-8x^2y+2xy^2=2x(4x^2-4xy+y^2)\)
\(=2x[(2x)^2-2.2x.y+y^2]=2x(2x-y)^2\)
21.
\((a^2+4)^2-16a^2b^2=(a^2+4)^2-(4ab)^2\)
\(=(a^2+4-4ab)(a^2+4+4ab)\)
25.
\(100a^2-(a^2+25)^2=(10a)^2-(a^2+25)^2\)
\(=(10a-a^2-25)(10a+a^2+25)\)
\(=-(a^2-10a+25)(a^2+10a+25)=-(a-5)^2(a+5)^2\)
29.
\(25a^2b^2-4x^2+4x-1=25a^2b^2-(4x^2-4x+1)\)
\(=(5ab)^2-(2x-1)^2=(5ab-2x+1)(5ab+2x-1)\)
1)
= ( a2 – 4 )( ab + 2b )
= ( a – 2 )( a + 2 ) + b ( a + 2 )
= ( a + 2 )( a – 2 + b )
2)
= ( x3 + 8 ) – ( 4x2 + 8x )
= ( x + 2 )( x2 – 2x + 4 ) – 4x ( x + 2 )
= ( x + 2 )( x2 – 2x + 4 – 4x )
= ( x + 2 )( x2 – 6x + 4 )
3)
= - ( y2 + 2yz – z2 ) + x2
= ( y2 – 2yz + z2 ) + x2
= ( y – z ) 2 + x2
= ( y – z – x )( y – z + x )